Manufacturing Natural Killer Cells as Medicinal Products - Chabannon, Christian; Mfarrej, Bechara; Guia, Sophie; Ugolini, Sophie; Devillier, Raynier; Blaise, Didier; Vivier, Eric; Calmels, Boris (Frontiers in Immunology, 2016)
Natural Killer (NK) cells are Innate Lymphoid Cells (ILC) with cytotoxic and regulatory properties. Their functions are tightly regulated by an array of inhibitory and activating receptors, and their mechanisms of activation strongly differ from antigen recognition in the context of HLA presentation as needed for T-cell activation. NK cells thus offer unique opportunities for new and improved therapeutic manipulation, either in vivo or in vitro, in a variety of human diseases, including cancers. NK cell activity can possibly be modulated in vivo through direct or indirect actions exerted by small molecules or monoclonal antibodies. NK cells can also be adoptively transferred following more or less substantial modifications through cell and gene manufacturing, in order to empower them with new or improved functions and ensure their controlled persistence and activity in the recipient. In the present review, we will focus on the technological and regulatory challenges of NK cell manufacturing, and discuss conditions in which these innovative cellular therapies can be brought to the clinic.